Healthcare simulation : a guide for operations specialists - Gantt, Laura, 1957-; Young, H. Michael, 1960- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
"With the growing use of simulation within the field of healthcare, Healthcare Simulation: A Guide for Operations Specialists provides a much needed resource for developing the roles and responsibilities of simulation operations specialists. The book illustrates the current state and evolution of the simulation professional workforce and discusses the topics necessary for the development of this pivotal role. The book promotes the value of simulation in healthcare and its associated outcomes while clarifying the operational requirements of successful simulations. Featuring numerous contributions from international experts, consultants, and specialists, Healthcare Simulation: A Guide for Operations Specialists presents advances in healthcare simulation techniques and also features:"--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Simulated patients; Medicine -- Study and teaching -- Simulation methods; Medicine -- Computer simulation; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Medicine -- Computer simulation; Medicine -- Study and teaching -- Simulation methods; Simulated patients; Education, Medical; Clinical Competence; Educational Technology; Health Personnel -- education; Patient Simulation; Electronic books